Pengaruh Model Tgfu (Teaching Games For Understanding) Terhadap Keterampilan Passing Dalam Permainan Sepakbola - Eris Febriansyah; Agustan, Boby; Rahman, Ramdhani (Journal of Physical Education and Sport Science, 2025)
Eris Febriansyah (NIM : 182223046), with the title "Influence Of The Tgfu Model On Passing Skills In The Football Game". 2022. The objectives to be achieved through this research are: to develop the TGfU training method to improve passing skills. This experimental study used a one-group pretest and posttest design. The study involved only one group. The effect can be known by comparing the test results before the treatment is given with the results of the tests carried out after the treatment is given. The population in this study found 18 people, with the sampling technique using total sampling using the entire population. Testing the normality of data distribution using the Kolmogorov-Smirnov Test withhe help of SPSS 25, with a significant value for pretest and posttest data of 0.056 and 0.102 greater than 0.05, then the data is normally distributed. Significant value for levene static 0.186> 0.05, then normally distributed. Furthermore, the calculated T obtained is -8.779 and for the t table is 1.73961. because the value of Tcount > Ttable, it can be said that there is an effect of the TGfU model training on passing skills in football games.